MASTER PLAN AND ITS ARACAJU CONTRADICTIONS: A PRELIMINARY ANALYSIS - Machado, Anselmo Belém (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
This article has as an initial objective to make a review to the Master Plan for Sustainable Urban Development in Aracaju. This paper also describes the issue of urban problems in the municipality of Aracaju in recent years. With the intense urban growth process, Aracaju has revealed the urgent need to be elaborated a master plan in a democratic manner, seeking a better quality of life of its population and an effective environmental protection. In relation to the current Master Plan for Sustainable Urban Development in Aracaju, we can say that this ‘plan is not flat nor full’, since this master plan reflects the interests of a privileged minority. Because we know that alteration and interference decisions in urban areas were defined to facilitate the producing agents of urban space and the privileged groups that are linked to these agents. Thus, this master plan is not full, since it favors the privileged minority of the population to the detriment of the majority excluded from basic rights expressed in the Federal Constitution of Brazil.